Geoelectrical monitoring of frozen ground and permafrost in alpine areas: field studies and considerations towards an improved measuring technology. Issue 1 (1st November 2013) - Supper, Robert; Ottowitz, David; Jochum, Birgit; Römer, Alexander; Pfeiler, Stefan; Kauer, Stefanie; Keuschnig, Markus; Ita, Anna
ABSTRACT: Processes that control permafrost warming in Alpine regions are still not completely understood. Recently, geoelectrical monitoring has emerged as a useful tool to investigate thawing and freezing processes. However, high resistive environments and harsh environmental conditions pose very unfavourable conditions for automated resistivity measurements. Based on the results of several test studies, an improved data acquisition system for geoelectrical monitoring of frozen soils was developed. Furthermore, the implementation of algorithms for statistical analysis of raw data time series led to a significant improvement in the reliability of inversion results. At two Alpine sites, namely Molltaler Glacier and Magnetkopfl/Kitzsteinhorn, the adapted system was tested at soil temperature conditions between 0°C and –12°C. Data was continuously collected at both locations over nearly a full seasonal cycle. The results showed an almost linear dependency of resistivity and temperature at values above –0.5°C. At lower temperatures, the relation was non‐linear, indicating that the reduction of porosity due to the shrinking of connected brine channels was the dominating process that determined the value of resistivity. Based on the derived results, further improvements were suggested, especially for measurements at soil temperatures below –4.5°C as low injection currents make it extremely challenging to gather these.